Evaluasi Kapasitas Saluran Drainase Sekunder di Jalan Kapten Pattimura Telanaipura Kota Jambi Menggunakan Software Hec-Ras - Freddy Ilfan; Ade Nurdin; Nadia Tristhayanti (Universitas Batanghari Jambi, 2023)
One of the areas in Jambi City that experience drainage system problems are the Telanaipura area, precisely on Jalan Kapten Pattimura. The area around the research site is a densely populated area and there are several shopping centers, restaurants, and a fairly high road user. When there is a large rain or rain for a long enough time, this area is often flooded with water as high as 0.2 - 0.8 meters which can cause quite a lot of losses for local residents and also for business owners in the area. From this, it can be said that the drainage channel at this location is less than optimal for collecting and draining rainwater discharge. In this case, it is necessary to conduct a study of hydrological analysis and hydraulics analysis of the drainage channel which is useful in helping to solve the problems that occur. This study used hydrological data in the form of monthly rainfall for the past 10 years and the geometry of secondary drainage channels on Jalan Kapten Pattimura Telanaipura. The method used in this study is in the form of hydrological analysis with the maximum rainfall method, gumbel, and calculation of plan discharge with a rational method. This Hydraulic analysis carried out uses the help of the HEC-RAS program to simulate the discharge of water flow in the drainage. Based on the results of the analysis, it can be concluded that the secondary drainage channel of Jalan Kapten Pattimura, Telanaipura District, Jambi City, cannot accommodate the flow discharge of the plan for periods 2, 5, and 10 years. This is due to sedimentation, high rainfall, suboptimal drainage channels in accommodating flow discharge, and the presence of piles of garbage. The solution to this problem is to deepen the dimensions of the drainage channel by 40–135 cm deep.